2007
DOI: 10.1002/jbm.b.30842
|View full text |Cite
|
Sign up to set email alerts
|

Heat denaturation of fibrinogen to develop a biomedical matrix

Abstract: Native and heat denatured fibrinogen are the basis for various matrices used to establish hemostasis as well as for constructing biomedical devices. For example, fibrin microbeads (FMB) prepared by a heated ( approximately 70 degrees C) oil emulsion process were reported to be attractive to mesenchymal-type cells, such as fibroblasts, endothelial and smooth muscle cells, and useful for isolating mesenchymal stem cells from bone marrow. Here, we examined the solution properties of fibrinogen subjected to heat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…We suspected the large difference in the amount of protein recovered was due to precipitation of fibrinogen in the plasma samples. Indeed, removal of the fibrinogen by pre-incubation at 56°C for 3 min (33,34) reduced the levels of extraneous protein in the acetate precipitated samples to levels comparable to those obtained for the serum samples with essentially no loss of exosomes. As discussed above, extraneous proteins in the exosome preparation should not pose any problems for transcriptomic analysis.…”
Section: Discussionmentioning
confidence: 77%
“…We suspected the large difference in the amount of protein recovered was due to precipitation of fibrinogen in the plasma samples. Indeed, removal of the fibrinogen by pre-incubation at 56°C for 3 min (33,34) reduced the levels of extraneous protein in the acetate precipitated samples to levels comparable to those obtained for the serum samples with essentially no loss of exosomes. As discussed above, extraneous proteins in the exosome preparation should not pose any problems for transcriptomic analysis.…”
Section: Discussionmentioning
confidence: 77%
“…Little denaturation by heat occurs during a fabrication step, but prepared microspheres still maintain its major functions. 26 By controlling stirring speed and heat, we could prepare the spherical microspheres with highly porous surface structure, offering cells sufficient space for attachment. 27 However, the differences between bare-Fbg microspheres and DOX-linker-Fbg microspheres were found on their surface density.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the conformational transformations of fibrinogen at these high temperatures, FMBs are highly haptotactic to various cell types, including osteogenic bone marrow-derived progenitors. 99,100 For bone tissue engineering studies, the obtained FMBs were incubated for 2 days in a suspension containing whole 97,98,101 Next, authors cultured FMB-MSCs constructs in osteogenic medium and obtained a bone-like structure which was implanted into a mouse skull defect. After 2 months, results showed that defects filled with bone-like tissue had a Ca/P ratio similar to that of the native bone while no repair was seen in the control animals without implants or when the defect was filled with FMBs alone.…”
Section: Different Forms Of Fibrin Applications In Bone Tissue Enginementioning
confidence: 99%